Single Cell Sequencing of the Pineal Gland: The Next Chapter - Coon, Steven L.; Fu, Cong; Hartley, Steven W.; Holtzclaw, Lynne; Mays, Joseph C.; Kelly, Michael C.; Kelley, Matthew W.; Mullikin, James C.; Rath, Martin F.; Savastano, Luis E.; Klein, David C. (Frontiers in Endocrinology, 2019)
The analysis of pineal cell biology has undergone remarkable development as techniques have become available which allow for sequencing of the entire transcriptome and, most recently, the sequencing of the transcriptome of individual cells. It has been possible to identify at least nine distinct cell types in the pineal gland of the rat, allowing for the first time identification of the precise cells of origin and expression of transcripts. Here the current state of knowledge generated by these transcriptomic efforts is reviewed, with emphasis on the highlights insights suggested by the findings.